The hexosemonophosphate shunt as an alternate metabolic pathway for conidial differentiation in Neurospora - G. Turian (Fungal Genetics Reports, 1962)
The hexosemonophosphate shunt as an alternate metabolic pathway for conidial differentiation in Neurospora